Patent law and biological inventions - Rimmer, Matthew (Annandale, N.S.W. : The Federation Press, 2006)
This collection considers a wide range of biological inventions - micro-organisms, plants and flowers, transgenic animals, genes, express sequence tags and research tools, as well as genetic diagnostic tests and pharmaceutical drugs
'Law in context special issue' -- Cover
Includes bibliographical references
Keywords: Biotechnology -- Patents; Patent laws and legislation